Levetiracetam induced drug reaction with eosinophilia and systemic symptoms (DRESS) - Elengoe, Asita; Jamil, Adawiyah; Goh, Siew Wen; Arumugam, Mohan; Ismail, Rasimah; Periyasamy, Petrick (Ministry of Health and Universiti Brunei Darussalem, 2019)
Drug reaction with eosinophilia and systemic symptom (DRESS) is a severe adverse drug reaction characterized by rash, fever, lymphadenopathy and internal organ involvement. Levetiracetam, a non-aromatic anti-epileptic drug is generally considered to be safe. Levetiracetam induced DRESS is rare. We report a 62- year-old male treated with levetiracetam for seizures secondary to brain abscess. He developed fever followed by rash and mild hepatitis. The rash resolved with lower dose of levetiracetam but other features including eosinophil count continued to worsen. There was marked resolution of symptoms after discontinuation of levetiracetam and systemic corticosteroid therapy. Rapid diagnosis and immediate cessation of the culprit drug is key to treatment of DRESS.